Plasma breakdown in sulfur hexaflouride and air mixtures for high voltage switch applications - Ronzone, Evan J., author; Yalin, Azer P., advisor; Williams, John D., committee member; Simske, Steven J., committee member (Colorado State University. Libraries, 2025)
High voltage spark gap switches are critical components used across a wide range of electrical systems where reliable switching and protection at high voltage is required. Power transmission and generation systems rely on such switches to protect systems in the event of switching surges, while also functioning as switching elements in high-voltage circuit breakers. High voltage spark gaps enable the controlled delivery of enormous amounts of electrical energy in very fast timescales. Such properties make spark gap switches highly desirable for pulsed power facilities such as Sandia National Laboratories Z-Machine. Across all applications, these switches must reliably hold off very high voltages on the order of hundreds of kilovolts, while maintaining accurate function. Switchgear must operate for long periods of time, with minimal maintenance. Spark gaps commonly use dielectric gas to insulate the electrodes and improve performance. Among such gases, sulfur hexafluoride (SF6) has been the preferred choice due to its excellent breakdown and recombination qualities. Sulfur hexafluoride possesses exceptional dielectric strength due to its large molecular size and high electronegativity, which allows it to effectively capture free electrons and prevent avalanche breakdown in high electric fields. Additionally, SF6 demonstrates superior recombination properties, as its dissociation products tend to recombine back into stable SF6 molecules, maintaining consistent gas composition and breakdown voltage over many switch closures. However, SF6 is also an expensive gas which presents significant supply chain challenges. SF6 also presents a major asphyxiation hazard in the event of a leak. Efforts to remove SF6 from current high voltage systems require significant design revisions and are difficult to implement quickly. A possible solution to reduce SF6 usage is to use a mixture of SF6 and zero-air (synthetic air nominally composed of 79% N2 and 21% O2, with trace impurities typically below 1 ppm total) at higher operating pressure. However, such mixtures do not yet have large amounts of data supporting their breakdown properties or long-term reliability. This thesis presents the design of an experimental system that measures the breakdown voltages of zero-air - SF6 mixtures at varying operating pressures and compositions. Long-term measurements of breakdown voltage stability and switch reliability using Weibull analysis are also presented. The theoretical background of Paschen's law is discussed, including linear approximations in high pressure-distance ranges. Significant efforts were undertaken to accurately measure the voltage immediately prior to breakdown by minimizing free variables and losses. New switch designs were created, and significant system alterations were made to improve data collection accuracy. System automation was enhanced to accommodate very long test series which would otherwise require significant manual labor over many days. Results indicate that relatively small concentrations of SF6 in gas mixtures significantly increase breakdown voltage compared to pure air. Furthermore, repeated breakdown testing of these mixtures demonstrates comparable, though slightly reduced, reliability compared to pure SF6. Future investigations examining breakdown products or electrode surface conditions could provide better understanding of the recombination dynamics in these mixed-gas systems.
Keywords: pulsed power; Paschen; sulfur hexafluoride